ANALISIS PERBANDINGAN PEMBIAYAAN BARANG MODAL ANTARA SEWA GUNA USAHA DENGAN PINJAMAN PERBANKAN DAN KAITANNYA DENGAN BIAYA PAJAK PADA PT. DUTA ABADI PRIMANTARA - Willy Hermawan (Jurnal Bina Akuntansi, 2019)
This study aims to determine ways of financing assets using bank credit or withleasing to a company, where the company opts for bank credit and leasing tomake income tax savings. The study was conducted at PT. Duta Abadi Primantarawith the calculation of fiscal costs and commercial costs with the type of casestudy research. The data obtained are primary data collected throughdocumentation obtained from the company. The data collected includescommercial and fiscal calculation reports. Based on research results obtainedthat the company chose financing of assets with leasing because it saves capital,flexible requirements, lower costs, ease of budgeting, profitable cash flow andalso inflation protection.